Quantification of large and middle proteins of hepatitis B virus surface antigen (HBsAg) as a novel tool for the identification of inactive HBV carriers. Issue 11 (26th September 2017) - Pfefferkorn, Maria; Böhm, Stephan; Schott, Tina; Deichsel, Danilo; Bremer, Corinna M; Schröder, Kathrin; Gerlich, Wolfram H; Glebe, Dieter; Berg, Thomas; van Bömmel, Florian
Abstract : Objective: Among individuals with chronic hepatitis B, those with hepatitis B e-antigen (HBeAg)-negative chronic hepatitis (CHB) can be difficult to distinguish from those with HBeAg-negative chronic HBV infection, also referred to as inactive HBV carriers (ICs), but both require different medical management. The level of HBV surface antigen (HBsAg) has been proposed as a marker to discriminate between chronic infection and hepatitis stages. HBsAg consists of large, middle and small HBs. The aim of this study was to determine whether the composition of HBsAg improved the identification of ICs among HBsAg-positive subjects with different phases of HBV infections. Design: HBV large surface proteins (LHBs) and HBV middle surface proteins (MHBs) were quantified in serum samples from 183 clinically well-characterised untreated patients with acute (n=14) HBV infection, ICs (n=44), CHBs (n=46), chronic HBeAg-positive phase (n=68) and hepatitis delta coinfection (n=11) using an ELISA, with well-defined monoclonal antibodies against the preS1 domain (LHBs) and the preS2-domain (MHBs). A Western blot analysis was used to verify the quantitation of the components of HBsAg. Total HBsAg was quantified using a modified commercially available assay (HBsAg V.6.0, Enzygnost, Siemens, Erlangen). Results: The composition of HBsAg showed specific patterns across different phases of hepatitis B. Individuals in the IC phase had significantly lower proportions of LHBs and MHBs than patients in acute or chronic phases irrespective of their HBV e-antigen status (p<0.0001) or HBsAg level. Both LHBs and MHBs ratios better predicted the IC phase than total HBsAg levels. Conclusion: Quantification of MHBs, particularly LHBs represents a novel tool for the identification of the IC stage.